Problems in the regulatory policy of the drug market - Nathália Molleis Miziara; Diogo Rosenthal Coutinho (Universidade de São Paulo, 2015)
OBJECTIVE Analyze the implementation of drug price regulation policy by the Drug Market Regulation Chamber. METHODS This is an interview-based study, which was undertaken in 2012, using semi-structured questionnaires with social actors from the pharmaceutical market, the pharmaceuticals industry, consumers and the regulatory agency. In addition, drug prices were compiled based on surveys conducted in the state of Sao Paulo, at the point of sale, between February 2009 and May 2012. RESULTS The mean drug prices charged at the point of sale (pharmacies) were well below the maximum price to the consumer, compared with many drugs sold in Brazil. Between 2009 and 2012, 44 of the 129 prices, corresponding to 99 drugs listed in the database of compiled prices, showed a variation of more than 20.0% in the mean prices at the point of sale and the maximum price to the consumer. In addition, many laboratories have refused to apply the price adequacy coefficient in their sales to government agencies. CONCLUSIONS The regulation implemented by the pharmaceutical market regulator was unable to significantly control prices of marketed drugs, without succeeding to push them to levels lower than those determined by the pharmaceutical industry and failing, therefore, in its objective to promote pharmaceutical support for the public. It is necessary reconstruct the regulatory law to allow market prices to be reduced by the regulator as well as institutional strengthen this government body.